Geroprotectors: A role in the treatment of frailty. (June 2019) - Trendelenburg, A.U.; Scheuren, A.C.; Potter, P.; Müller, R.; Bellantuono, I.
Highlights: The number of people with frailty is increasing due to the longevity revolution. Frailty has severe impact on the quality of life of older people and on the health and social care costs. Geroprotectors have the potential to delay, halt or reverse frailty. The challenges in clinical trial design are the lack of an agreed definition of frailty, animal models, patients' selection criteria and outcomes measure. Abstract: The proportion of the population over the age of 65 is growing the most rapidly due to the longevity revolution. Frailty is prevalent in this age group and strongly associated with disability and hospitalization, having a significant impact on the costs of health and social care. New effective interventions to delay or reverse frailty are urgently required. Geroprotectors are a new class of drugs, which target fundamental mechanisms of ageing and show promise in delaying the onset of or boosting resilience in frail older people. However, there are challenges to their clinical translation. Here we review the literature for evidence that frailty can be delayed or reversed and geroprotectors can improve frailty in murine models and in patients. We will then discuss the challenges, which make their clinical testing complex and propose potential options for moving forward.